2016
DOI: 10.1164/rccm.201510-2091oc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Drug Resistance in Mycobacterium tuberculosis and Their Diagnostic Value

Abstract: Rationale: The development of molecular diagnostics that detect both the presence of Mycobacterium tuberculosis in clinical samples and drug resistance-conferring mutations promises to revolutionize patient care and interrupt transmission by ensuring early diagnosis. However, these tools require the identification of genetic determinants of resistance to the full range of antituberculosis drugs.Objectives: To determine the optimal molecular approach needed, we sought to create a comprehensive catalog of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(188 citation statements)
references
References 43 publications
6
180
2
Order By: Relevance
“…Publicly released in 2008, the TB Drug Resistance Mutation Database (TBDReaMDB) was one of the earliest centralized databases compiling potential resistance-associated mutations from a systematic literature review, providing a valuable resource for molecular M. tuberculosis diagnostics and further research in this field (38). Since the initial release of TBDReaMDB, efforts to build upon this data set to construct curated databases linking genotype data with phenotypic DST results have been undertaken and are critical to improving the accuracy of molecularbased susceptibility profiling (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Publicly released in 2008, the TB Drug Resistance Mutation Database (TBDReaMDB) was one of the earliest centralized databases compiling potential resistance-associated mutations from a systematic literature review, providing a valuable resource for molecular M. tuberculosis diagnostics and further research in this field (38). Since the initial release of TBDReaMDB, efforts to build upon this data set to construct curated databases linking genotype data with phenotypic DST results have been undertaken and are critical to improving the accuracy of molecularbased susceptibility profiling (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in various settings (of which the cited are a few) have demonstrated this to be the case, 25;28;29;4955 (including enrichment of katG mutations in MDR versus non-MDR INH resistant strains 20;25;28;29;56 ). The ‘spectrum’ of mutations observed in MDR strains varies from setting to setting, however, and may be linked to the dose of INH used for treatment 54 and the clonal spread of different mutations.…”
Section: From Inh Resistance To Multidrug Resistancementioning
confidence: 97%
“…20 Lack of clarity about the association between specific mutations, phenotypic resistance, and treatment outcomes hinders genotyping being used to make rapid treatment decisions. 21;22 inhA mutations are generally associated with lower phenotypic resistance than katG mutations, 23;24 but even within the same gene different mutations can cause differing levels of phenotypic resistance.…”
Section: Resistance Mutationsmentioning
confidence: 99%
“…The most frequently observed cause of resistance are SNPs in genes encoding drug targets or converting enzymes, but large deletions might also result in resistance. 71,241 A summary of loci implicated in resistance to antituberculosis drugs is presented in table 4. A review of the loci is not included in this Commission, and for a comprehensive list of resistancecausing mutations (1325 polymorphisms [SNPs and indels] at 992 nucleotide positions from 31 loci, 6 promoters, and 25 coding regions) and corresponding aminoacid changes, we refer the reader to the London School of Hygiene & Tropical Medicine TB Profiler.…”
Section: Genotypic Testingmentioning
confidence: 99%